Atomic Observation of the Al2Cu Interface in Cu/Al Shaped Charge Liners. Issue 3 (5th January 2023) - Zhang, Jinhong; Sun, Chunhao; Shao, Ruiwen; Dong, Weikang; Liu, Tiansheng
Abstract: Shaped charge liners have recently received a lot of attention due to their exceptional properties, particularly copper–aluminum (Cu–Al) bimetal liners which cause larger penetration than copper liners. However, inevitably high brittle compositions exist along the interface such as Al2 Cu and Al4 Cu9 which induce low plasticity to negatively influence the performance. Until now, the interface structure between these compositions and Cu/Al has seldom received attention. In this paper, the interface between Al2 Cu and Cu/Al is depicted and studied on atomic level. Aberration‐corrected scanning transmission electron microscopy (STEM) and energy dispersive spectrometry (EDS) reveal that the Al2 Cu are the main compositions of Alx Cu along Cu/Al interface. Importantly, the interface structure of Al2 Cu–Cu and Al2 Cu–Al is demonstrated, where the Al2 Cu–Cu interface has a transition region showing polycrystalline, while the Al2 Cu–Al interface exhibits a sharp boundary which can form a 5 nm width co‐exist area in which Al2 Cu and Al both exist without any mismatch or dislocation. The findings certify the discrepant atomic structure in the interface which can help understanding the connection style of highly brittle compositions and Cu/Al. This phenomenon has potential value in understanding the Cu/Al liner's performance and Cu/Al alloys in the future. Abstract : The interface composition of Cu/Al shaped charge liners is mostly made up of Al2 Cu, and it is directly illustrated that the interface of Al2 Cu–Cu presents transition and polycrystal areas, and Al2 Cu–Al presents sharp boundary that can form a 5 nm width co‐existing area that has not been reported before.